DESCRIBING THE EVOLUTION OF MEDICATION USE OVER TIME IN PEOPLE LIVING WITH DEMENTIA USING NETWORK ANALYSIS. (20th December 2022) - Emdin, Abby; Boblitz, Alexa; Maclagan, Laura; Bethell, Jennifer; Watt, Jennifer; Harris, Daniel; Maxwell, Colleen; Bronskill, Susan
Abstract: Prescribing for community-dwelling older adults living with dementia is complex. Multiple medications may be used to manage symptoms associated with dementia and/or co-existing chronic conditions, and can lead to problematic polypharmacy. Our objective was to use network analysis, a data science method, to provide a comprehensive description of co-prescribed medications in persons with dementia and describe whether these patterns change over time. We created a population-based cohort of community-dwelling older adults (aged 67+ years) in Ontario, Canada, newly diagnosed with dementia (between April 2014 and January 2019), from health administrative data, and developed medication networks at one year prior to, at, and for up to five years following dementia diagnosis. Among 136, 292 individuals newly diagnosed with dementia, the mean age was 82.2 years and 59% were female. The most common medication subclasses dispensed at diagnosis were primarily cardiovascular medications: statins (45.6%), proton pump inhibitors (27.3%), beta-blockers (27.0%), calcium blockers (25.1%), and ACE inhibitors (24.6%). Similar proportions of medication subclasses were found at five years after diagnosis, except cholinesterase inhibitors (34.0% at five years were dispensed cholinesterase inhibitors compared to 16.9% at diagnosis). The most frequent co-prescribed medication pairs at diagnosis included statins and beta-blockers (16.0%), proton pump inhibitors (16.0%), and ace inhibitors (15.4%), respectively. Co-prescription was similar at five years, but also included higher frequency of co-prescribing with cholinesterase inhibitors (e.g., 19.4% were prescribed cholinesterase inhibitors and statins). Network diagrams demonstrate the complexity of prescribing in this population and highlight concurrent prescribing which may require careful monitoring or deprescribing.